One parameter family of S-tangent surfaces - Körpınar, Talat; Turhan, Essin (UNIV ESTADUAL MARINGA, PRO-REITORIA PESQUISA POS-GRADUACAO, 2015)
In this paper, we study S - tangent surfaces according to Sabban frame in the Lorentzian Heisenberg group H. We obtained differential equations in terms of their geodesic curvatures in the Lorentzian Heisenberg group H. Finally, we found explicit parametric equations of one parameter family of S. tangent surfaces according to Sabban Frame.
Keywords: biharmonic curve; Heisenberg group; geodesic curvature; fluid flows